Feasibility pilot of an adapted parenting program embedded within the Thai public health system - Amalee McCoy; Jamie M. Lachman; Catherine L. Ward; Sombat Tapanya; Tassawan Poomchaichote; Jane Kelly; Mavuto Mukaka; Phaik Yeong Cheah; Frances Gardner (BMC, 2021)
Abstract Background This feasibility pilot of the Parenting for Lifelong Health for Young Children program in Thailand aimed to: 1) explore the feasibility of study evaluation approaches; 2) assess the feasibility of delivering an adapted program; 3) report indicative effects on child maltreatment and related outcomes; and 4) examine intervention content associated with key mechanisms of change perceived by caregivers and facilitators. Method Sixty primary caregivers of children aged 2-9 years were recruited for an 8-week parenting program embedded within the local health system. Mixed-methods approaches included quantitative caregiver-report and observational data from standardized instruments, and qualitative data from individual and group interviews with caregivers and program facilitators. Analyses involved Wilcoxon signed-rank tests, paired t-tests, Friedman's ANOVA, and thematic analysis. Results Participants reported that most (65%) were grandparents or great-grandparents. Study retention and response rates were high, and enrolled caregivers attended an average of 93% of sessions. Primary outcomes showed caregiver-reported pre-post reductions in overall child maltreatment (d = − 0.58, p < 0.001), as well as reductions in physical (d = − 0.58, p < 0.001) and emotional abuse (d = − 0.40, p < 0.001). Combined caregiver report and observational assessments using the HOME Inventory showed reductions in abusive and harsh parenting (d = − 0.52, p < 0.001). Secondary outcomes demonstrated decreases in child neglect; dysfunctional parenting; poor child monitoring and supervision; parental sense of inefficacy; child behavior problems; daily report on child problem behavior; parent overall depression, anxiety, and stress; and attitudes supporting physical punishment and harsh discipline. There were increases in overall positive parenting, daily positive parenting behavior, as well as HOME Inventory assessments on parent-child relationships. Thematic analyses from interviews and focus group data identified six key program themes associated with strengthened parent-child relationships, reduced child behavior problems, improved attitudes and strategies toward discipline, and improved management of parental stress. Conclusions This study represents one of few evaluations to test the feasibility of an evidence-based parenting program embedded within routine public health service delivery in a low- or middle-income country. Findings show preliminary effectiveness in reducing child maltreatment, improvements on 22 of 24 secondary outcomes, and perceived mechanisms of change that support quantitative findings. Prospects are promising for program scalability, pending randomized controlled trial results. Trial registration 11/01/2019, ClinicalTrials.gov, ID# NCT03539341 .